Didactic Audiovisual Translation and Foreign Language Education - Talaván, Noa; Lertola, Jennifer (Routledge research in audiovisual translation, 2024)
This book offers an updated and comprehensive view of the possibilities of didactic audiovisual translation (didactic AVT or DAT) in language education, by presenting the methodological bases that support its pedagogical use at all levels of linguistic proficiency, as well as in different educational stages and contexts. The volume defines the main didactic AVT modes, accompanied by general recommendations, specific guidelines, complete sample lesson plans and sequences, and models for assessment. Didactic AVT is described in this book as an effective pedagogical resource that can improve students' language competence and trigger core factors in education, such as learners' motivation and engagement in language classes, their cognitive processes, their creativity, and the active use of ICTs in the classroom. From the perspective of educators, DAT provides a pool of multipurpose resources that may help them to enrich their classes from a pedagogical, linguistic and intercultural standpoint. This book will be a valuable resource for graduate students, scholars, and practitioners in translation studies, particularly those interested in audiovisual translation and foreign language learning.